Young Learners’ Early Linguistic Stage: Phonological Processes in Islamic Kindergarten - Kirana, Khalida; Susanto (UIN Salatiga, 2025)
This study aims to identify the factors influencing pronunciation ability and to analyze the types of phonological processes performed by young learners of English. Employing a qualitative case study design, this research involved three students aged 4 to 5 years from Khalifah Kindergarten, an Islamic early childhood education institution in Tulungagung, where English instruction is integrated with Islamic values in the curriculum. Data collection methods included classroom observations, interviews, and audio recordings. Data analysis was conducted following Miles and Huberman’s interactive model. The findings reveal that several factors influence young learners’ ability to pronounce English vocabulary, including early exposure to the language, parental support, the use of learning media, flexible timing, motivation, and the school environment. The analysis identified various phonological processes performed by the subjects, such as decentralization, centralization, epenthesis, palatal fronting, cluster simplification, liquidization, vowel alteration and consonants addition. Notably, decentralization and centralization emerged as the most frequently used processes, indicating that vowel sound modification is a prevalent strategy among children as they adjust their articulation skills. The theoretical implications of these findings align with Khan and Lewis’ phonological processes theory and reinforce the language acquisition theory of Piaget, Vygotsky, and Krashen, demonstrating that children's phonological development is influenced by cognitive maturity and social interaction. Empirically, this research contributes to the advancement of effective learning methods and enriches the understanding of foreign language acquisition in early childhood.